Influence of habitat change from land to sea on the evolution of antimicrobial peptide gene families, including β‐defensin gene clusters, in mammals. (8th November 2020) - Kang, Mingue; Ahn, Byeongyong; Yum, Joori; Cho, Hye‐sun; Choi, Munjeong; Hong, Kwonho; Choi, Youngsok; Kim, Jin‐Hoi; Park, Chankyu
Abstract: Antimicrobial peptides (AMP) are innate immune molecules with antimicrobial activity that are important to defend against pathogenic infection. We performed genome‐level analyses of the AMP family gene repertories for six terrestrial ( Homo sapiens, Bos taurus, Sus scrofa, Capra hircus, Canis lupus, and Loxodonta africana ) and five aquatic ( Balaenoptera acutorostrata, Tursiops truncatus, Lipotes vexillifer, Odobenus rosmarus, and Trichechus manatus ) mammals and identified 59 (30 partial or pseudogenes) previously unannotated β‐defensin ( BD ) sequences from those aquatic species. Extreme reduction in BD genes was evident in Odontoceti. NK‐lysin and granulysin among AMP family genes were absent from aquatic mammals, except O. rosmarus . A phylogenetic tree constructed with 296 amino acid sequences of BD from 11 species suggested a broad expansion of this gene family with extensive genetic diversity in mammals. We determined a pair of evolutionarily conserved flanking genes for each of four BD containing intervals and defined them as PGK2‐TFAP2D, BCL2L1‐ZCCHC3, AGPAT5‐GPM6A, and ADAM29‐CTSB intervals. The characterization of BD syntenic regions revealed conservation of homologous synteny blocks and reuse of evolutionary breakpoint regions. Phylogenetic reconstruction of BD gene evolution showed that the major expansion events of BD genes occurred four times in the mammalian lineage. Taken together, the findings of this study show the occurrence of significant differences in the number of AMP family genes in diverse mammalian species, including aquatic species, likely due to their environmental adaptation. Abstract : We performed genome‐level analyses of the antimicrobial peptide (AMP) family gene repertories for six terrestrial and five aquatic mammals and identified 59 previously unannotated β‐defensin ( BD ) sequences from the aquatic species. Extreme reduction in BD genes was found in Odontoceti. The characterization of BD syntenic regions revealed conservation of homologous synteny blocks. Our findings show the occurrence of significant differences in the number of AMP family genes in diverse mammals, including aquatic species, likely due to their environmental adaptation.